Ultrasound-Guided Nerve Block for Inguinal Hernia Repair: A Randomized, Controlled, Double-Blind Study. Issue 5 (1st September 2012) - Bærentzen, Finn; Maschmann, Christian; Jensen, Kenneth; Belhage, Bo; Hensler, Margaret; Børglum, Jens
Abstract : Background and Objectives: Open inguinal hernia repair in adults is considered a minor surgical procedure but can be associated with significant pain. We aimed to evaluate acute postoperative pain management in male adults randomized to receive an ultrasound-guided ilioinguinal and iliohypogastric nerve block administered before surgery, in addition to a standard analgesic regimen. Methods: Sixty patients were included in this randomized, controlled, and double-blind study. Patients were randomized to the administration of a block with 20 mL bupivacaine 0.5% or a placebo block with 20 mL saline. The primary outcome measure was pain at mobilization in the postanesthesia care unit (PACU). Pain at rest, dermatomal anesthesia, time spent in the PACU/ward, opioid consumption, postoperative vomiting and nausea, ability to perform activities of daily living, and perceived ill health status were secondary outcomes. Results: A significant reduction in pain scores at mobilization ( P <0.001) and rest ( P < 0.005) was recorded in the bupivacaine group upon arrival in the PACU and again after 30 minutes. Pain at rest was similarly reduced in the bupivacaine group at the time of discharge ( P < 0.017). There were significantly fewer patients ( P < 0.05) with severe (numerical rating scale >5) and moderate (numerical rating scale >3) pain at mobilization and rest, respectively. Opioid consumption and time spent in the PACU were not significantly different between groups. Conclusions: Ultrasound-guided blocks of the ilioinguinal and iliohypogastric nerves resulted in a statistically significant and clinically relevant reduction in postoperative pain in the PACU both at mobilization and at rest.